Detection of the Deformation of an Intelligent Textile in a Specific Point - JosÃƒÂ© Gisbert; Vicente Cambra; Jordi Margalef; Francesc Escudero; Maria Alsina (Sensors, 2007)
An intelligent textile is a textile structure that measures and reacts in front of external agents or stimulus with or without integrated electronic equipment. . The finality of the present textile is to take one more step towards intelligent textile, considering the integration of electronics and textile needs, to be industrially viable and to keep up the necessary competitiveness, raising the final price as little as possible. The finality of these experiments is to develop a textile that varies in conductivity and resistance in relation to the elongation of the textile, detecting changes caused by the alteration of a piece of clothing, from the pressure of a finger on the material, for example. One of the most important characteristics of textile is the capacity of reproducing measures, of varying the response in different tests. Two lines of research were opened: the study of the most adequate structure to achieve a response that can be reproduced and the study of the best way of taking measures without altering the behavior of the textile.